Nilai-nilai Pendidikan Karakter dalam Naskah Drama Anak-Anak Kerajaan Burung Karya Saini KM - Monica Novriyenti; Syeilendra Syeilendra (Institut Nalanda, 2024)
This research aims to describe the values of character education in the children's drama script of the Kingdom of Birds by Saini KM. The object used in this study is the script of the drama Kingdom of Birds by Saini KM which contains the values of character education. This type of research is qualitative research using the content analysis method. The data collection technique is to read and understand the script of the drama Kingdom of the Bird by Saini KM with the aim of obtaining a clear understanding of the drama script, identifying dialogues or actions that have character education values in the script of the drama Kingdom of Birds by Saini KM, recording data related to character education values on the record sheet and inventorying the data that has been obtained in the form of a table format. The data analysis technique is to classify data regarding the character education values contained in the script of the drama Kingdom of Birds by Saini KM in the form of a data recording format, clarify or clarify the data that has been obtained, interpret the data regarding the values of character education in the script of the drama Kingdom of Birds by Saini KM and draw conclusions and report the results of data analysis. Based on the results of the data analysis, it was found that the values of character education in the script of the drama Kingdom of Birds by Saini KM, namely the values of character education (1) religious, (2) honest, (3) hard work, (4) democratic, (5) appreciating achievements, (6) friendly/communicative, (7) love of peace, (8) caring for the environment, (9) caring for social, and (10) responsibility.